Listening to/at/with Marilyn Lerner’s "They’re All in Families" - McNeilly, Kevin (Critical Studies in Improvisation / Études critiques en improvisation, 2008)
Marilyn Lerner’s audio-art composition “They’re All in Families” (1998) re-works a sound clip from a virulently homophobic message left on an answering machine, turning hate-speech back on itself to expose the rhythms and textures of verbal violence.